Making Sense of U.S. Trade Policy: What Recent Negotiations Can Tell Us. (2019) - Manak, Inu
Abstract : U.S. trade policy is not what it used to be. Since the U.S. withdrawal from the Trans-Pacific Partnership in January 2017, Indo-Pacific trade relations have been in constant flux. It is not clear where U.S. trade policy will end up, particularly with regard to its relationship with China. However, the conclusion of two renegotiations of previous U.S. trade agreements can tell us generally about the new U.S. approach and what this means for our trading partners. I will discuss developments from the renegotiation of the Korea-U.S. free trade agreement (KORUS) and the U.S.-Mexico-Canada Agreement (USMCA) as a replacement for the North American Free Trade Agreement (NAFTA).